2020
DOI: 10.2139/ssrn.3622985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Working Memory Training on Children’s Cognitive and Noncognitive Skills

Abstract: Working memory capacity is thought to play an important role for a wide range of cognitive and noncognitive skills such as fluid intelligence, math, reading, the inhibition of pre-potent impulses or more general self-regulation abilities. Because these abilities substantially affect individuals' life trajectories in terms of health, education, and earnings, the question of whether working memory (WM) training can improve them is of considerable importance. However, whether WM training leads to improvements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 72 publications
4
18
0
Order By: Relevance
“…Our finding of transfer to mathematical learning is consistent with some prior studies [19][20][21] but is at odds with some others, the largest negative study being that by Roberts and colleagues 31 . One reason for the discrepancies could be that the current study included a general population while the study by Roberts et al included only children with low WM capacity (lowest 15th percentile).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of transfer to mathematical learning is consistent with some prior studies [19][20][21] but is at odds with some others, the largest negative study being that by Roberts and colleagues 31 . One reason for the discrepancies could be that the current study included a general population while the study by Roberts et al included only children with low WM capacity (lowest 15th percentile).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown a positive impact of rotation training on mathematics [13][14][15] while others found no effect [16][17][18] . Similarly, training of vs-WM improves mathematical outcomes in children in some studies [19][20][21] , although there are also negative findings 22,23 . Given these mixed results, some suggest that cognitive training, in general, does not transfer at all to academic abilities 24 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Berger et al . ( 2020 ) reported an improvement index of 20.76 points in children functioning at a lower or average neurocognitive level. Furthermore, they found that training effects did not differ significantly between children functioning at a lower neurocognitive level and those who had an average level (Berger et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by recent research suggesting that cognitive gains following CogmedRM training may have substantial immediate impacts on academic success and self-regulation, as well as lasting impacts on individuals' life trajectories, health, education, and earnings. 34 Ultimately, training these skills may contribute to an improved quality of life for children and adolescents with NF1.…”
Section: Discussionmentioning
confidence: 99%